Perceived availability and access limitations to ecosystem service well-being benefits increase in urban areas - Marie Lapointe (Resilience Alliance, 2020)
Access mechanisms can determine the benefits that people derive from a given ecosystem service supply. However, compared to ecosystem service availability, access has received little research attention. The relative importance of availability compared to access in limiting ecosystem service benefits is even less well understood. In cities, the observed disconnect between people and nature might result in part from changes in ecosystem service availability and access compared to rural areas. To address these research gaps, we compared perceived limitations to ecosystem service well-being benefits in urban and rural areas in the Solomon Islands. We predicted that more people would report being limited in ecosystem service benefits in urban than rural areas. Drawing on data from 200 respondents, we found that more urban dwellers reported being limited in both availability and access to the benefits that they derived from ecosystem services. Availability factors were the most frequently perceived limitations, although access played an important role for both provisioning and cultural services. In urban areas, poorer people, women, and older people identified the most limitations. Findings show the importance of investigating both ecosystem service availability and access to manage the environment in a way that sustains or increases benefits to people.